2009
DOI: 10.1111/j.1464-410x.2009.08419.x
|View full text |Cite
|
Sign up to set email alerts
|

A prospective, non‐randomized trial comparing robot‐assisted laparoscopic and retropubic radical prostatectomy in one European institution

Abstract: RESULTSWe enrolled 105 patients in the RRP and 103 in the RALP group; the two groups were comparable for all clinical and pathological variables, except median age. For RRP and RALP the respective median operative duration was 135 and 185 min ( P < 0.001), the intraoperative blood loss 500 and 300 mL ( P < 0.001) and postoperative transfusion rates 14% and 1.9% ( P < 0.01). There were complications in 9.7% and 10.4% of the patients ( P = 0.854) after RRP and RALP, respectively; the positive surgical margin rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
184
3
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 199 publications
(201 citation statements)
references
References 26 publications
6
184
3
6
Order By: Relevance
“…The difference in 1-year complications between the groups was primarily due to the significantly higher rate of bladder neck contractures in the ORP group (5 vs. 1%, p = 0.018). In a prospective study of 103 RALP and 105 ORP patients (study period: 2006–2007), Ficarra et al also found similar complication rates[19]. The 30-day unadjusted complication rate for RALP was 10% compared to 11% for ORP ( p = 0.85).…”
Section: Comparison and Discussion Of Orp And Ralpmentioning
confidence: 81%
See 4 more Smart Citations
“…The difference in 1-year complications between the groups was primarily due to the significantly higher rate of bladder neck contractures in the ORP group (5 vs. 1%, p = 0.018). In a prospective study of 103 RALP and 105 ORP patients (study period: 2006–2007), Ficarra et al also found similar complication rates[19]. The 30-day unadjusted complication rate for RALP was 10% compared to 11% for ORP ( p = 0.85).…”
Section: Comparison and Discussion Of Orp And Ralpmentioning
confidence: 81%
“…Similarly, Schroeck et al from Duke University reported no difference in the positive surgical-margin rate of 362 RALP patients and 435 ORP patients (29 vs. 28%, p = 0.7)[35]. In a single-institution study, Ficarra and colleagues also found no difference in the positive surgical-margin rates between RALP and ORP (34 vs. 30%, p = 0.97)[19]. In their subset analysis of patients with pathologic organ-confined disease, the rate of surgical-margin positivity was the same for both groups (12%).…”
Section: Comparison and Discussion Of Orp And Ralpmentioning
confidence: 99%
See 3 more Smart Citations